Charles-Louis Montesquieu’s Social Views on The Laws Of Human Nature as A Paradigm Of Peace - Sharipov Dilshod Baxshilloyevich (Indonesian Journal Publisher, 2025)
This article analyzes the philosophical views of the French Enlightenment thinker Charles-Louis de Montesquieu on the state of nature and natural laws. Montesquieu explained the fundamental laws of human nature through four main principles, highlighting their essence and role in the formation of society. According to the author, in the state of nature, humans strive for peace, tend toward cooperation, and naturally develop social ties. Additionally, the article explores Montesquieu’s critique of Thomas Hobbes’ ideas and the differences between his views on the state of nature and those of other Enlightenment thinkers. The research also examines the assessment of Montesquieu’s legacy by representatives of the French sociological school. This study holds significant importance from the perspectives of law, philosophy, and sociology, providing a deeper understanding of the state of nature and the formation of society throughout human history